Study in Perfect - Gorham, Sarah, 1954- (Book collections on Project MUSE., 2014)
Study in Perfect is an exploration of perfection. In ""Moving Horizontal"" a Victorian house loses its charm over time, especially when compared to a modernist contemporary filled with light. Family life is dense with pleasure, as in the perfect vacation described in ""Marking Time in Door County, "" and in ""Neriage, or What Is the Secret of a Long Marriage, "" where an ancient Japanese ceramic technique has much in common with shaping a close relationship. There is such a thing as a perfect cup of tea, depending on who is preparing and drinking it (""Perfect Tea""). And schmaltzy show tunes fl.